2016
DOI: 10.1161/circheartfailure.115.002081
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase 4 Inhibition Alleviates Shortage of Circulating Glucagon-Like Peptide-1 in Heart Failure and Mitigates Myocardial Remodeling and Apoptosis via the Exchange Protein Directly Activated by Cyclic AMP 1/Ras-Related Protein 1 Axis

Abstract: This study was conducted to address the essential effect of the DPP4i on myocardium in terms of cardiac function and remodeling using nondiabetic mice with pressure overload (thoracic aortic constriction [TAC]). We unexpectedly found the pathological decline in casual GLP-1 level with concomitant reduction of its second messenger cyclic AMP (cAMP) concentration in myocardium of TAC, which was prevented by ALO. In the context of exploring the molecular mechanism(s) underlying the GLP-1/cAMP pathway, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…Emerging evidence suggests that DPPIV inhibitors, also known as gliptins, may provide cardiovascular benefits beyond glycemic control (1,3,4,13,23,40). In fact, genetic deletion or pharmacological inhibition of DPPIV improves cardiovascular outcomes after myocardial infarction in both normoglycemic and diabetic mice (42).…”
Section: This Study Shows That Dipeptidyl Peptidase IV (Dppiv) Inhibimentioning
confidence: 99%
“…Emerging evidence suggests that DPPIV inhibitors, also known as gliptins, may provide cardiovascular benefits beyond glycemic control (1,3,4,13,23,40). In fact, genetic deletion or pharmacological inhibition of DPPIV improves cardiovascular outcomes after myocardial infarction in both normoglycemic and diabetic mice (42).…”
Section: This Study Shows That Dipeptidyl Peptidase IV (Dppiv) Inhibimentioning
confidence: 99%
“…Thus, the macrophage content in atherosclerotic plaques is an important contributor to atherosclerotic plaque instability. For above reasons, it is extremely urgent and necessary to develop effective molecular imaging 64 Cu-TNP by the aortic root and arch in atherosclerotic arteries model of apoE -/-mice, which was further demonstrated on in vivo MRI imaging (Fig. 1).…”
Section: Imaging Of Atherosclerosis and Vulnerable Plaquementioning
confidence: 99%
“…Ciesienski et al described the synthesis of three new fibrin-targeted PET probes: FBP1, FBP2 and FBP3, and then using them to image arterial thrombus in the rat models by using in vivo PET/MRI. Three fibrin-specific target peptides were labeled with 64 Cu after the conjugation with 1, 4,7, 10-tetraaza-cyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA). For MR angiography imaging, the results showed that there was an occlusion in the right carotid artery at the site of crush injury, and this vessel occlusion corresponds to the high radioactivity uptake displayed on PET images [32] (Fig.…”
Section: Imaging Of Thrombusmentioning
confidence: 99%
See 2 more Smart Citations